Marketing of Imported Agricultural Products and Its Effects on Producers and some Hinterlands (UPN) Households in the City of Kinshasa/RDC from 2012 to 2018 - Bwama Meyi, Marcel; Ruremesha, Sylvestre; Maseka, W.; Bitwakamba, Grégoire Mashala; Ciminello, Romeo (European Journal of Sustainable Development, 2019)
Our goal was to understand the behavior of sellers and consumers of imported agricultural products (corn, rice, chicken and pork) vis-à-vis local products. To test our hypotheses, we used methods of analysis and surveys using documentary techniques and the interview. The results reveal that 4.4% of respondents say they buy imported rice because it is cheaper and is found in abundance; 22.4% say it is of better quality and 6.9% say it is in good taste. This confirms our first hypothesis. Our analysis shows that 70.7% of respondents believe that local cereals are of better quality and 29.3% of respondents believe that imported cereals are not better. 58.6% of respondents prefer imported fresh food; 39.9% prefer local fresh food and 1.7% did not give their opinion.The vast majority, 86.2% of the respondents, want local products to be sold by the producers themselves, 5.2% want it to be a farm product and 3.4% to have a local brand. These results support the sustainable economy in the community. However, 22.4% of respondents complain of being exposed to cholesterol which can lead to cardiovascular diseases in the short and long term following consumption of live spawns without prior checks of health and public health officials; on the other hand 77.6% are abstraction, following the precariousness of life and poverty in Kinshasa. At the national level, taking into account the agricultural sector is inevitable for sustainable development. The state must take responsibility by feeding its own population with organic products of good quality. So, we must work and invest in the agricultural sector in the DRC, to reduce the food and economic dependence that the country is going through. The tax policy on imported fresh food would be one way to support local production and reduce imports so much that makes the balance of trade deficit in the DRC. Keywords: Marketing, imported agricultural products, Hinterlands households, Kinshasa, DRC